2015
DOI: 10.1016/j.drugalcdep.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cannabis involvement and suicidal thoughts and behaviors

Abstract: Background In the present study, we examined the relationship between cannabis involvement and suicidal ideation (SI), plan and attempt, differentiating the latter into planned and unplanned attempt, taking into account other substance involvement and psychopathology. Methods We used two community-based twin samples from the Australian Twin Registry, including 9,583 individuals (58.5% female, aged between 27 and 40). The Semi-Structured Assessment of the Genetics of Alcoholism (SSAGA) was used to assess cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 47 publications
(65 reference statements)
7
28
0
Order By: Relevance
“…Importantly, future efforts should be targeted at understanding the role of both depression and impulsivity (Turecki, 2005), especially when considering the relationship between SA and substance involvement. For instance, studies have reported stronger associations between unplanned SA and substance involvement (Borges et al, 2010b; Delforterie et al, 2015) indicating the potential role of impulsivity but a more systematic investigation of potential mediators and modifiers is necessary. Finally, from a clinical perspective, our results suggest that in individuals at high familial risk for substance involvement, a history of SA should be viewed as a potential harbinger of escalating substance use, potentially leading to dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, future efforts should be targeted at understanding the role of both depression and impulsivity (Turecki, 2005), especially when considering the relationship between SA and substance involvement. For instance, studies have reported stronger associations between unplanned SA and substance involvement (Borges et al, 2010b; Delforterie et al, 2015) indicating the potential role of impulsivity but a more systematic investigation of potential mediators and modifiers is necessary. Finally, from a clinical perspective, our results suggest that in individuals at high familial risk for substance involvement, a history of SA should be viewed as a potential harbinger of escalating substance use, potentially leading to dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that smokers with severe nicotine dependence are more likely than non-smokers to report more frequent and serious SA (Berlin et al, 2015;Lopez-Castroman et al, 2016). Some longitudinal studies have found profound elevations in risk for SI and SA in chronic, heavy and early-onset cannabis users (Delforterie et al, 2015;Silins et al, 2014;van Ours et al, 2013) while other studies have attributed these associations to confounding measures (Price et al, 2009), thus the evidence is inconclusive (Borges et al, 2016). In contrast to this literature, little is known about whether SI and SA are themselves associated with the onset of substance use and substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other prospective work supports that more frequent cannabis use is related to greater odds of SI and suicide attempt from age 14 to 21 (Fergusson et al, 2002) and from age 21 to 27 (Pedersen, 2008). The relation between cannabis use and SI remains after controlling for co-occurring psychopathology and other relevant variables (e.g., adverse events) (Delforterie et al, 2015; Fergusson et al, 2002; Pedersen, 2008; van Ours et al, 2013). Notably, SI does not prospectively predict cannabis use (van Ours et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, due to lack of power, it was not possible to examine potential differences in the link between EAU and subgroups of individuals engaging in SA. Previous work has established that cannabis use is associated with increased odds for SA, but only for unplanned rather than planned attempts (Delforterie et al 2015). Therefore, it may be the case that other substance use, such as EAU, may be related to certain types of SA.…”
Section: Discussionmentioning
confidence: 99%